Effects of Appendectomy on the Onset and Course of Ulcerative Colitis in Chinese Patients. (6th November 2018) - Chen, Dafan; Ma, Jing; Luo, Shengzheng; Lu, Lungen; Wan, Xinjian; Ben, Qiwen
Abstract : Background . Previous epidemiological studies have suggested that appendectomy may be a protective factor against the development of ulcerative colitis (UC). However, the results of these studies were inconsistent, with rare studies in Chinese populations. Aim . This study examined the associations between appendectomy performed before UC diagnosis and the occurrence and clinical course of UC in Chinese patients. Methods . A case control study was conducted to compare the rate of appendectomy between UC patients and controls matched for age and sex at two Chinese hospitals. Clinical course of UC was compared between UC patients who underwent appendectomies before UC diagnosis and who did not. Results . 402 UC patients and 402 controls were included. The percentage of appendectomy performed before UC diagnosis in UC patients did not differ significantly from controls (2.74% vs 3.98%, P = 0.442 ). Subgroup analysis on the basis of localization of UC patients did not find significant difference from controls. The extent of disease involvement in UC patients who underwent appendectomy was smaller than patients who did not (P = 0.009 ). Appendectomy was found to be significantly related to the location of the disease independent of smoking status in multivariate analysis (P < 0.001 ). Appendectomy did not influence severity of disease and need for immunosuppressive treatment or colectomy. Conclusion . We did not find a significant negative association between appendectomy and the UC occurrence in Chinese patients. Appendectomy performed before UC diagnosis may reduce the extent of UC involvement.